Histostereological effect of Rosemarinus officinalis L. on gentamicin induced acute kidney injury among adult male albino rats (Rattus norvegicus) - Waswa, Kennedy W. (International Journal of Research in Medical Sciences, 2025)
Background: Acute kidney injury (AKI) is a worldwide public health defy associated with high morbidity, mortality, and high healthcare costs in developing countries. Gentamicin (GN) is an affordable and efficacious first-line drug for managing all gram-negative bacteria, especially in low-income populations. Rosmarinus officinalis (RO) is a natural antioxidant can be used to stop upshots of AKI. The study was done to determine the histo-stereological effect of RO on GN induced acute kidney injury among adult male albino rats of Rattuss norvegicus species. Methods: Post-test only true experimental design was used; 25 adult male Albino rats were simple randomly divided into five groups each having 5 Albino rats. Control group received rat pellets plus water ad libitum, GN (100 mg/kg/bwt/i.p.), low dose RO (100 mg/kg/bwt/p.o. + GN), medium RO (150 mg/kg/bwt/p.o. + GN), and high dose RO (200 mg/kg/bwt/p.o. + GN) groups. GN was administered intraperitoneal, and RO given orally for seven consecutive days. After completion of 24 hours of the last dose administration, they were humanely sacrificed, and kidney were harvested for histo-stereology studies. Results: There was no significant difference observed between the high dose RO and the control group. The glomerulus volume of the high dose RO and the controls were comparable unlike for the low and medium doses RO groups. Conclusions: The study established that co- administration of high dose (200 mg/kg/bwt) of RO with gentamicin can effectively prevent kidney structures damage that is associated with gentamicin drug toxicity.